Husband's Support for Wife Who Experience Ca Mamae at Haji Adam Malik Hospital Medan - Indra Hizkia Peranginangin; Helinida Saragih; Ronita Reksawana Hutagalung (Lembaga Pengembangan Kinerja Dosen, 2025)
Husband support is a very important factor for women suffering from breast cancer, where husband support consists of instrumental, informational, judgmental/appreciative and emotional support. This study aims to find out the husband's support for wives who experience Ca Mamae at Haji Adam Malik Hospital Medan in 2024. The research design used is descriptive research. The sampling technique used purposive sampling with a sample of 41 respondents. The instrument used was a questionnaire sheet. The results of the study based on the dimension of instrumental support were in the category of adequate, 51.2% of the research results were in the category of adequate, the results of the research based on the dimension of appraisal support/appreciation in the category of 61% were in the adequate, the results of the research based on the dimension of emotional support showed the adequate-category of 51.2%, the overall level of support of the husband to the wife who experienced ca mamae showed that around 56, 2% in the good category. The results of the study can be concluded that the more family support increases, the more patients suffering from breast cancer can undergo their treatment with enthusiasm. Researchers suggest that families increase their husband's support for wives who have breast cancer.